GLOBALIZATION, DEVELOPMENT AND STRUCTURAL REFORMS. AFRICA AND THE PAES IN THE 80s - Rossi, Ignacio Andrés (2021)
This paper proposes to address the context and application of the Economic Stabilization and Structural Adjustment Plans (saps) implemented in the African continent during the 1980s. The aim of this work is to dialogue with three facets of analysis, based on the literature and the reports on the subject: globalization, indebtedness, and implementation of economic stabilization plans. To do this, different works on the subject are analyzed and contrasted according to the structure of the proposal. It has been found that the sapsconstitute a first order element to explain part of the economic future in the region.